Classification of Mild Stroke: A Mapping Review. Issue 9 (28th May 2019) - Schwartz, Jaclyn K.; Capo‐Lugo, Carmen E.; Akinwuntan, Abiodun Emmanuel; Roberts, Pamela; Krishnan, Shilpa; Belagaje, Samir R.; Kovic, Mark; Burns, Suzanne Perea; Hu, Xiaolei; Danzl, Megan; Devos, Hannes; Page, Stephen J.
Abstract : Persons with mild stroke experience motor and cognitive impairments that negatively affect their health and quality of life. To address these deficits, it is essential for clinicians and researchers to precisely identify mild stroke survivors. Despite the fact that half of all strokes are categorized as mild, no standards exist on what constitutes a "mild" stroke. The purpose of this study is to summarize the current classification of mild stroke using a mapping review approach. Strategies to categorize "mild stroke" severity were explored in 188 papers indexed in the PubMed database. The results indicate that there was substantial variability in the procedures and scoring criteria used to determine mild stroke. To identify persons with mild stroke, researchers have largely applied assessment instruments developed to inform acute stroke care (eg, National Institutes of Health Stroke Scale, Modified Rankin Scale, Barthel Index). Unfortunately, these approaches demonstrate floor effects and fail to detect the long‐term disabling impairments that often limit the outcomes of mild stroke survivors. Additional research is warranted to suggest an evidence‐based mild stroke categorization strategy that enhances diagnosis, treatment, and referral decisions to the benefit of mild stroke survivors.